Temporary agency work in the SOEP: Coping with data quality problems - Holger Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In principle, the SOEP is a highly adequate data source for analyzing the socio-economic background of temporary agency workers. In this paper, it's argued that on second glance, the SOEP's temp worker variable shows severe problems with data quality. An easy-to-use adjustment procedure is proposed that alleviates the problem, but is not an encompassing solution. Therefore, it is concluded that in the long term, the questionnaire needs to be improved.
Keywords: C83; J53; 330; temporary agency work; panel surveys